Unresolved World War II Animosity Dampens Empathy Toward 2011 Japanese Earthquake and Tsunami. (February 2014) - Yang, Ying; Liu, Xiao-xiao; Fang, Yang; Hong, Ying-yi
The 2011 Japanese earthquake and tsunami evoked widespread empathy and sympathy. We examine how historical representations of WWII among Chinese and Americans affect their empathy toward the Japanese disaster. In three online surveys conducted 8 days, 4 weeks, and 10 months after the Japanese earthquake, we recruited over 900 participants from diverse age groups and geographic locations in China and the United States. We consistently found that the Chinese participants showed less empathy toward the Japanese disaster (but not toward the 2004 Indian Ocean Tsunami) than did Americans, and these cross-national differences were partially mediated by Chinese participants' tendency to attribute the disaster to retribution or associate Japan as an aggressor in WWII. We also manipulated participants' identity (national vs. global identity) and found it had an interaction effect with patriotism on empathy toward the Japanese. We discuss how these findings shed light on identity, patriotism, shared historical representations, and lingering international conflicts.